Stellar populations, stellar masses and the formation of galaxy bulges and discs at z < 3 in CANDELS. Issue 4 (13th October 2017) - Margalef-Bentabol, Berta; Conselice, Christopher J.; Mortlock, Alice; Hartley, Will; Duncan, Kenneth; Kennedy, Rebecca; Kocevski, Dale D.; Hasinger, Guenther
Abstract: We present a multicomponent structural analysis of the internal structure of 1074 high-redshift massive galaxies at 1 <  z  < 3 from the CANDELS HST Survey. In particular, we examine galaxies best fitted by two structural components, and thus likely forming discs and bulges. We examine the stellar mass, star formation rates (SFRs) and colours of both the inner 'bulge' and outer 'disc' components for these systems using Spectral Energy Distribution (SED) information from the resolved ACS+WFC3 HST imaging. We find that the majority of both inner and outer components lie in the star-forming region of UVJ space (68 and 90 per cent, respectively). However, the inner portions, or the likely forming bulges, are dominated by dusty star formation. Furthermore, we show that the outer components of these systems have a higher SFR than their inner regions, and the ratio of SFR between 'disc' and 'bulge' increases at lower redshifts. Despite the higher SFR of the outer component, the stellar mass ratio of inner to outer component remains constant through this epoch. This suggests that there is mass transfer from the outer to inner components for typical two-component-forming systems, thus building bulges from discs. Finally, using Chandra data we find that the presence of an active galactic nucleus is more common in both one-component spheroid-like galaxies and two-component systems (13 ± 3 and 11 ± 2 per cent) than in one-component disc-like galaxies (3 ± 1 per cent), demonstrating that the formation of a central inner component likely triggers the formation of central massive black holes in these galaxies.